Heavy minerals in use - Mange, Maria A.; Wright, David T. (Developments in sedimentology, 2007)
The book is structured thematically, encompassing principles, processes and products, practice and applications. Discussion of processes that control heavy mineral assemblages throughout the rock cycle are presented by leading experts, whose key-note works are followed by specialist case studies. Each work also provides details on the geology of the study area, techniques and data treatment. The high number of contributions represent the collective experience and wisdom of generations of geologists, and provide an invaluable source of references to works carried out in many parts of the world. * Presents a unique and authoritative resource of immediate relevance and practical use to the researcher and applied geologist * Contains case studies demonstrating the broad range of applications of heavy minerals in a variety of modern and ancient geological settings, and in resource exploration * Includes examples of geological problems from employing heavy mineral analysis and establishing criteria that can be applied before deciding to undertake a study.